2021
DOI: 10.3390/foods10122978
|View full text |Cite
|
Sign up to set email alerts
|

Nature’s “Free Lunch”: The Contribution of Edible Insects to Food and Nutrition Security in the Central Highlands of Madagascar

Abstract: Edible insects are a healthy, sustainable, and environmentally friendly protein alternative. Thanks to their quantitative and qualitative protein composition, they can contribute to food security, especially in Africa, where insects have been consumed for centuries. Most insects are still harvested in the wild and used for household consumption. So far, however, little attention has been paid to insects’ real contribution to food security in low-income countries. Entomophagy, the human consumption of insects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…On the other hand, caterpillars have been noted to contain a high percentage of protein, fat, unsaturated fatty acids, mineral salts (iron, calcium and zinc) and various categories of vitamins [ 12 , 20 , 28 ]. A 100g sample of caterpillars was found to contain 76% of the daily nutrient intake requirements of adults [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, caterpillars have been noted to contain a high percentage of protein, fat, unsaturated fatty acids, mineral salts (iron, calcium and zinc) and various categories of vitamins [ 12 , 20 , 28 ]. A 100g sample of caterpillars was found to contain 76% of the daily nutrient intake requirements of adults [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Sub-Saharan Africa contributed to a third of undernourished children globally [ 10 ], while 14 million were estimated to be experiencing conditions characterised by acute malnutrition [ 11 ]. Meanwhile, in the southern Africa region, Madagascar has been experiencing child-stunted growth and malnutrition, as one-third of men and women are anaemic [ 12 ]. This, therefore, shows that there is an urgent need to identify sustainable food systems with the capacity to produce sufficient food quantities to meet the needs of the growing population [ 7 ], while having minimal environmental destruction, for example, entomography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower-income people in South Africa consume more edible insects, most likely because they save money on food when insects are readily available (Egan, 2013). Similarly, Dürr and Ratompoarison (2021) found no significant differences in insect consumption between poorer and wealthier families in Madagascar highlands because insects are not purchased but instead collected in the wild. Meanwhile, in China and Kenya, income does not affect the frequency of consumption of edible insects (Liu et al, 2020;Carolyne, 2018).…”
Section: Factors Affecting the Consumption Of Edible Insectsmentioning
confidence: 94%
“…A more traditional investigation was that by Dürr and Ratompoarison [ 20 ], who provided evidence for the importance of food insects in the local diet of rural communities in the central highlands of Madagascar. The investigation showed that the insects contributed significantly to the animal protein uptake of the local population, especially in the humid season, when other protein sources were scarce.…”
mentioning
confidence: 99%